The influence of work motivation and compensation employee performance at the office of transportation agency in North Tapanuli Regency North Sumatra Province - Gabriel Panggabean; Herayati Herayati; Martinus Wahyu Purnomo (Junal Ilmu Manajemen, 2023)
Performance evaluation is the outcome of employees' efforts and serves as the foundation for assessing the outcomes of their work. The level of employee performance is directly correlated with the developmental outcomes of the organization. Conversely, subpar performance can adversely affect an organization's growth. Two key factors that impact employee performance are job motivation and compensation. This study aims to investigate the effects of job motivation and compensation on employee performance within the North Tapanuli District Transportation Agency office. It is a quantitative descriptive study employing the explanatory survey approach. Data for the study were collected through questionnaires distributed to 41 respondents. The analysis involved various tests, including validity and reliability assessments, multiple linear regression analysis, correlation coefficient examination, determination coefficient analysis, normality test, multicollinearity test, heteroskedasticity test, autocorrelation test, and partial (t) and simultaneous (f) hypothesis testing, all conducted using SPSS 25. The research findings reveal a noteworthy impact of both job motivation and compensation on employee performance. The coefficient of determination test illustrates that job motivation and compensation collectively contribute to 70.6% of employee performance variation, signifying a substantial influence of these factors on employee performance at the North Tapanuli District Transportation Agency office.